(1456) دراسة تحليلية للموارد الأرضية والزراعيةفى ج.م.ع بحث التوطن الصناعى فى مصر حتى عام 2000 An analytical study of land and agricultural resources in Egypt; research on industrial localization in Egypt up to the year 2000 - عبد الله الدعوشي (معهد التخطيط القومي, 2026)
تُعد هذه الورقة البحثية دراسة تحليلية شاملة للموارد الأرضية والزراعية في مصر ضمن إطار بحث "التوطن الصناعي حتى عام 2000". يسلط البحث الضوء على التحدي المتمثل في ندرة الأراضي الصالحة للزراعة وانحصارها في وادي النيل، مع رصد دقيق لظاهرة الزحف العمراني وتجريف التربة التي تلتهم آلاف الأفدنة سنوياً. كما يتناول الملف استراتيجيات التوسع الأفقي واستصلاح الأراضي، موضحاً خطط الدولة لزيادة الرقعة الزراعية في مناطق مثل سيناء والصحراء الغربية، وتصنيف الأراضي المصرية وفق جودتها وخصوبتها لضمان التوزيع الأمثل للموارد المائية المحدودة وتحقيق التكامل بين القطاعين الزراعي والصناعي. ويقدم البحث تحليلاً إحصائياً دقيقاً للتوزيع الإقليمي للمحاصيل الزراعية الرئيسية (الشتوية والصيفية والنيلية) على مستوى المحافظات، مع تتبع تطور إنتاجيتها خلال الفترة من 1976 إلى 1983. وتبرز الدراسة محافظات بعينها كمراكز ثقل زراعي، مثل الشرقية في إنتاج القمح، والدقهلية وكفر الشيخ في الأرز، والمنيا في محاصيل السكر والفول. وتهدف هذه البيانات إلى توفير قاعدة معرفية لصناع القرار لتحديد أنسب المواقع للتوطن الصناعي القائم على التصنيع الزراعي، مع التركيز على تحسين كفاءة الري واستخدام مياه الصرف المعالجة لمواجهة تناقص نصيب الفرد من الأراضي الزراعية وتلبية احتياجات النمو السكاني المتزايد. This research paper is a comprehensive analytical study of land and agricultural resources in Egypt within the framework of the "Industrial Localization until 2000" research project. The study highlights the challenge of the scarcity of arable land, which is concentrated in the Nile Valley, while also closely monitoring the phenomenon of urban sprawl and soil erosion that consumes thousands of acres annually. The paper also addresses strategies for horizontal expansion and land reclamation, outlining the state's plans to increase agricultural land in areas such as Sinai and the Western Desert. It classifies Egyptian lands according to their quality and fertility to ensure the optimal allocation of limited water resources and achieve integration between the agricultural and industrial sectors. The research provides a detailed statistical analysis of the regional distribution of major agricultural crops (winter, summer, and Nile crops) at the governorate level, tracking the development of their productivity during the period from 1976 to 1983. The study highlights specific governorates as agricultural powerhouses, such as Sharqia in wheat production, Daqahliya and Kafr El-Sheikh in rice production, and Minya in sugar and fava bean production. This data aims to provide a knowledge base for decision-makers to identify the most suitable locations for industrial settlement based on agro-processing, with a focus on improving irrigation efficiency and using treated wastewater to address the decreasing per capita share of agricultural land and meet the needs of increasing population growth.